THE EFFECTS OF BUSINESS STRATEGIES ON GROWTH OF MARKET SHARE IN THE TELECOMMUNICATIONS INDUSTRY IN KENYA: A CASE STUDY OF TELKOM KENYA - Ndambuki, Andrew; Bowen, Dr. Michael; Karau, Dr. James (European Journal of Business and Strategic Management, 2017)
Purpose: To analyze the business strategies of Telkom Kenya Limited and how this has helped the company gain market share. Methodology: The study adopted a descriptive research design. Findings: The results from the study show that the effects of strategies to gain market share have been successful. Strategies such as culture change, retrenchment, product differentiation, product modification, and aggressive marketing campaigns have had a major impact on the market share of the company. Further results show that the strategies at Telkom Kenya positively affect the company profits. Unique contribution to theory, practice and policy: The findings of this study will benefit a number of interest groups. Foremost, the management of Telkom Kenya Limited as a reference point will benefit from the research and recommendations on areas to improve on. Secondly, the study will benefit managers of other firms who can learn from the TKL case. For academicians, my research will contribute to the general body of knowledge and form a basis for further research on the effects of business strategies on any given industry. Investors, shareholders, suppliers and the general taxpaying public can also gain insight on the company and its strategic position within the mobile industry which can assist them in determining the viability of their investments. Finally, the government can also use the results to monitor how the industry is performing and help it formulate policies and mechanisms that will assist in expanding it in order to improve revenue collections in terms of taxes.